Predictors of non-remission of depression in a palliative care population. (1st April 2011) - Goodwin, L; Lee, W; Price, A; Rayner, L; Monroe, B; Sykes, N; Hansford, P; Higginson, I J; Hotopf, M
Abstract : Abstract: Introduction and aims: Prospective studies of depression in palliative care are rare. Two studies which examine depression prospectively in patients with advanced disease have not looked at predictors of remission. This study aims to explore prospective predictors of non-remission of depression in palliative care. Methods: The study design comprised two data collections: with initial assessment on referral to a palliative care service in South London, UK and a 4-week follow-up. 76 participants met the criteria for 'any depressive syndrome' at the time 1 assessment using the PRIME-MD, who also participated at time 2. The outcome measure was remission (N=39) or non-remission (N=37) of depression by time 2. Results: The findings showed that reporting low social support at time of referral was the most powerful risk factor for non-remission. There was also a strong association between improved physical symptoms, from time 1 to 2, and remission of depression. Conclusion: This study in palliative care is the first of which we are aware to explore factors associated with non-remission of depression. Depressed patients identified with low social support on referral to palliative care might particularly benefit from additional psychosocial care in the treatment of their depression. This study provides evidence that effective physical symptom management in palliative care may be a valuable intervention for depressive symptoms.